Unemployment and productivity growth: An empirical analysis within the augmented Solow model - Michael Bräuninger; Markus Pannenberg (Deutsches Institut für Wirtschaftsforschung (DIW), 2000)
Does a country's level of unemployment have an impact on the long-run growth rate? Incorporating unemployment into a generalised Solow-type growth model yields some answers. In the traditional Solow model, unemployment has no long-run influence on the growth rate and the level of productivity. The long-run level of productivity is reduced if higher unemployment leads to less formal education or to less learning-by-doing. If we allow for endogenous growth, unemployment reduces long-run productivity growth. Using panel data from 13 OECD countries from 1960 to 1990, we find evidence that an increase in unemployment scales down the long-run level of productivity.
Keywords: O40; O57; E24; 330; Growth; Equilibrium Unemployment; Panel Data